Effects of challenge with Clostridium perfringens, Eimeria and both on ileal microbiota of yellow feather broilers - Feng, Xin; Li, Tonghao; Zhu, Hui; Liu, Lidan; Bi, Shengqun; Chen, Xiaolin; Zhang, Huihua (Frontiers in Microbiology, 2022)
In the poultry industry worldwide, Clostridium perfringens has been causing major economic loss as it can cause necrotic enteritis (NE). The coccidial infection has been considered as the most important predisposing factor of NE caused by C. perfringens. In this study, we aimed to advance our knowledge on ileal microbiota of yellow feather broilers under C. perfringens and/or Eimeria challenge. Total of 80 healthy day old yellow feather broilers were randomly assigned to four groups including: Control, C. perfringens challenge group (C. Per), Eimeria challenge group (Cocc), and C. perfringens plus Eimeria challenge group (Comb). On day 14, the Cocc and Comb group broilers were orally gavaged 1 ml PBS solution containing 25,000 oocysts of Eimeria brunetti and 25,000 oocysts of Eimeria maxima. Starting on day 17, the C. Per and Comb group broilers were orally gavaged 10 mL of C. perfringens per bird (4 × 107 CFU/mL, ATCC® 13124™ Strain) every day for 6 days. 16S rRNA gene sequencing was performed on extracted DNA of ileal digesta samples. The results showed that C. perfringens alone did not affect the alpha diversity of ileal microbiome in yellow feather broilers but co-infection with Eimeria significantly decreased the diversity of ileal microbiota. C. perfringens and Eimeria challenge also decreased the relative abundance of beneficial bacteria including Bacteroidetes at the phylum level and Faecalibacterium at the genus level. At the species level, the relative abundance of Candidatus Arthromitus was significantly decreased in the Eimeria challenged groups. This microbial shift information of ileal microbiota under C. Perfringens and Eimeria challenge provide important reference data for the development of therapeutic approaches to necrotic enteritis in yellow-feather broiler chickens.